An unusual case of malignant esophago-pulmonary fistula secondary to esophageal carcinoma (Indian Journal of Case Reports, 2018)
Esophageal cancer is an aggressive cancer and has a poor survival rate. An esophago-pulmonary fistula is a rare complication of this cancer. This fistula causes pulmonary abscess formation and death in most patients. We are reporting a case of esophago-pulmonary fistula in a 55-year-old male patient who presented to us with complaints of fever and cough with expectoration. Chest radiographs initially showed right upper lobe consolidation which further progressed to cavitation and later on contrast-enhanced multi-detector computed tomography scan was used to diagnose this condition. An esophago-respiratory fistula is a rare complication of esophageal cancer, and esophago-pulmonary fistula is an even rarer subtype of this complication. It is essential to diagnose this condition early to avoid development of further complications and death.